Pelatihan Teknis Pemanfaatan Jagung Kering Menjadi Pakan Ikan dan Tepung untuk Kemandirian Ekonomi Masyarakat di Desa Tanah Seribu Kecamatan Binjai Selatan - Hilda Zahra Lubis; Raisah Armayanti Naution; Ijar Salna; Lu’lu Rahmadanti; Nur Sa’adah (BADAN PENERBIT STIEPARI PRESS, 2025)
This training activity aims to enhance students' knowledge through community service activities in collaboration with farmer groups in Tanah Seribu Village, Pasar 3 Dalam, Environment VII, South Binjai, focusing on corn waste utilization. The research was conducted on July 17, 2024. The resource persons in this study were Mr. Susanto and Mrs. Juliyanti. The approach methods for implementing the activities were interviews, discussions, and training. The corn harvest yield during dry season is approximately 300 kg, while during rainy season it reaches around 700 kg. Farmers only use dried corn to sell to agents. The fertilizers used are urea and poska. Through direct training methods, 80% of participants demonstrated the ability to distinguish between young and dried corn, harvest corn from plants, and separate corn kernels from cobs. This training provides significant benefits in developing knowledge about corn processing into fish feed and flour, while also contributing to community economic independence through the utilization of local agricultural products.